Stanovení vysoce těkavých chlorovaných uhlovodíků ve skládkových vodách metodou plynové chromatografie s plamenově-ionizačním detektorem s využitím mikroextrakce do xylenu - Kuráň, Pavel; Janoš, Pavel (Chemické listy, 2008)
To fulfil the requirements of health regulations and water quality, it is necessary to monitor the concentrations of volatile hydrocarbons in water at rather low levels. A simple and rapid GC-FID method utilizing liquid-liquid microextraction with xylene in closed vials for the determination of ten selected volatile chlorinated hydrocarbons in water before and after remediation was developed. The procedure allowed to determine selected hydrocarbons at concentrations 10?20 µg l-1 using 1000-ml samples or 30?50 µg l-1 using 60-ml samples. A significant decrease in the detection limits to 2?20 µg l-1 (for 60-ml samples) was achieved by lowering the noise level after replacing GC gases by higher-purity gases and using 1-chloropropane as internal standard. The determination of CHCl3 and CCl4 at the µg l-1 levels was feasible using an ECD detector. Even lower detection limits can be achieved by modification of the GC injector and by injecting a large volume of the xylene extract.
Keywords: financování organizované; Flame Ionization; plamínková ionizace; látky znečišťující vodu; Water Pollutants; Financing, Organized; halogenované uhlovodíky; Sewage; Hydrocarbons, Halogenated; odpadní vody